Sound Forge 8 essential training - Rountree, Thei.; Safari eBooks ([S.l.] : Total Training, 2009)
"Sound Forge is considered the industry standard for audio software professionals who want to create and edit digital audio files with absolute speed and precision. Acclaimed for its power, stability, and no-nonsense interface, it's the fastest way to get from raw audio to finished master. Sound Forge software contains everything you need to analyze, record and edit audio, produce music loops, digitize and clean-up old recordings, model acoustic environments, create streaming media and master replication-ready CDs. This training will help you master the basics and beyond. We will focus on the powerful Sound Forge Audio Editor, professional audio recording techniques, obtaining pristine audio quality, achieving professional audio effects and learning the audio restoration tools"--Resource description page.
Title from resource description page (viewed Oct. 2, 2009).
System requirements: Adobe Flash Player, version 8 or higher; or QuickTime Player, version 7.2 or higher; or Windows Media Player, version 11 or higher.
Electronic reproduction.
Keywords: Sound Forge; Digital audio editors; Software sequencers; Music -- Computer programs; Electronic books